The Effect Of Adding Egg White On The Physical And Organoleptic Properties Of Grape Juice (Vitis Vinifera, L.) - Domingos Taeque; Domingos Cairesi B. B. Gomes; Americo Pereira da Cruz (Eduvest - Journal of Universal Studies, 2024)
Grapes (Vitis vinifera L) are a recommended fibrous food, advised to be consumed in quantities of 300g – 400g per capita per day. Grapes are popular due to their delicious, sweet, and fresh taste, and their high nutritional content, especially vitamins C and A. The method used in this research is an experimental method with a Completely Randomized Design (CRD), consisting of 5 treatments with one factor. The results of these 5 treatments were then analyzed using analysis of variance (ANOVA), and if there were significant differences between treatments, they were further tested with the Least Significant Difference (LSD) test at a 5% significance level. The results of adding egg white to grape juice processed into grape juice were analyzed with the following average values: color with an average value ranging from 2.20 (A) to 3.40 (E), aroma with an average value ranging from 2.07 (A) to 3.60 (B), taste with an average value ranging from 2.20 (A) to 4.20 (C), and viscosity with an average value ranging from 1.93 (A) to 4.33 (C). This research shows that the best formulation for making grape juice (Vitis vinifera L) with the addition of 36 ml or 14.4% egg white (albumin), 250 grams of grapes, 500 grams of granulated sugar, and 2500 ml of distilled water has the highest score of 15.19 compared to other treatments.